Significance of Influencing Factors’ Relationship in Education Domain - Ruby, Jai; David, K (International Journal of Computer Sciences and Engineering, 2025)
In recent years, Educational Data Mining has developed into a research realm. All educational institutions are striving hard to prove themselves as the best to attract the student community. Academic performance of the students plays a vital role in determining the status of the institution. So, all the institutions strive hard to know their wards in advance and improve their performance to stand out among their competitors. Unfortunately most the information in the academic institutions are hidden and need to be extracted out. Data mining is a well known technique for bringing out the hidden potential of the institutions. For mining, the data need to be transformed and reduced for better performance. This model is mainly focused on finding out the significance of the relationship between the derived influencing factors.